The Rationality of Weber's Actions and Changes in Community Behavior (Case Study of Behavior Change in the Arrangement of the Benoyo Spring Area) (Forum Ilmu Sosial, 2022)
Before the City without Slums Program (Kotaku) arrangement and its community by the Department of Housing and Settlement, the Benoyo spring area was not well-preserved and poorly maintained. This study aims to discover what induced the behavior changes after implementing Kotaku. The researcher found it interesting as changing behavior is not something that could be easily accomplished. This research was conducted at the Benoyo spring in Ngentak Kutowinangun Lor Salatiga using qualitative methods with descriptive research. The results of this study reaffirm Max Weber’s statement that change can occur because it is based on value rationality. The value given in the Kotaku program is commensurate with the values already existing in society. It is synonymous with when Max Weber explained the growth of capitalism in Germany as the ethical values of Protestant religion (inner-worldly). The old (traditional) rationality has been replaced by value rationality, followed by objective and instrument rationality. This research thus shows the importance of value rationality in changing behavior.